Governance of artificial intelligence and data in Australasian higher education : A snapshot of policy and practice. - Selvaratnam, Ratna; Venaruzzo, Lynnae (Australasian Council on Open, Distance and e-Learning (ACODE), 2024)
In October 2023, ACODE conducted a survey to get an understanding of Artificial Intelligence (AI) policy and practice in Australasian universities. The results show there is a mixed view whether guidelines and policies are in place with respect to the governance of AI and data which suggests the sector needs to continue these conversations for some time to come. Furthermore, ethical application of AI is emerging through experimental activities and pilots of proof of concepts, suggesting that case studies and recommendations for practice could be developed in 2024 to further assure quality and equity in education. [Publisher summary, ed]